Bet v 1 – a Trojan horse for small ligands boosting allergic sensitization?. Issue 8 (August 2014) - Asam, C.; Batista, A. L.; Moraes, A. H.; de Paula, V. S.; Almeida, F. C. L.; Aglas, L.; Kitzmüller, C.; Bohle, B.; Ebner, C.; Ferreira, F.; Wallner, M.; Valente, A. P.
Summary Background Birch pollen allergy represents the main cause of winter and spring pollinosis in the temperate climate zone of the northern hemisphere and sensitization towards Bet v 1, the major birch pollen allergen, affects over 100 million allergic patients. The major birch pollen allergen Bet v 1 has been described as promiscuous acceptor for a wide variety of hydrophobic ligands. Objective In search of intrinsic properties of Bet v 1, which account responsible for the high allergenic potential of the protein, we thought to investigate the effects of ligand‐binding on immunogenic as well as allergenic properties. Methods As surrogate ligand of Bet v 1 sodium deoxycholate (DOC) was selected. Recombinant and natural Bet v 1 were characterised physico‐chemically as well as immunologically in the presence or absence of DOC, and an animal model of allergic sensitization was established. Moreover, human IgE binding to Bet v 1 was analysed by nuclear magnetic resonance (NMR) spectroscopy. Results Ligand‐binding had an overall stabilizing effect on Bet v 1. This translated in a Th2 skewing of the immune response in a mouse model. Analyses of human IgE binding on Bet v 1 in mediator release assays revealed that ligand‐bound allergen‐induced degranulation at lower concentrations; however, in basophil activation tests with human basophils ligand‐binding did not show this effect. For the first time, human IgE epitopes on Bet v 1 were determined using antibodies isolated from patients' sera. The IgE epitope mapping of Bet v 1 demonstrated the presence of multiple binding regions. Conclusions and clinical relevance Deoxycholate binding stabilizes conformational IgE epitopes on Bet v 1; however, the epitopes themselves remain unaltered. Therefore, we speculate that humans are exposed to both ligand‐bound and free Bet v 1 during sensitization, disclosing the ligand‐binding cavity of the allergen as key structural element.